PENANAMAN MANGROVE SEBAGAI UPAYA PELESTARIAN LINGKUNGAN LAUT DESA TANJUNG BUNGA, KECAMATAN WAWOLESEA, KONAWE UTARA - Sjamsu Alam Lawelle; Azwar Sidiq; Chairun Annisa Aryanti; Yustika Intan Permatahati; Wa Ode Intiyani Mangurana (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia is one of the countries with extensive mangrove forests, covering around 22.8% of the world's total mangrove area. Mangrove ecosystems are a natural resource that plays an important role in human survival, and their existence is crucial in maintaining ecological balance in coastal areas. In addition, mangroves also play a significant role in the economy. This activity has a specific goal of preserving the mangrove ecosystem and maintaining the marine environment, particularly in the coastal area of Tanjung Bunga Village, North Konawe. This activity is carried out in four stages, namely: observation, program planning, mangrove socialization, and mangrove planting. The mangrove planting was carried out with the direct assistance of the National Collaboration Community Service Team, Faculty of Fisheries and Marine Sciences, Halu Oleo University. This activity can provide enormous benefits for the coastal environment, especially in helping to restore the condition of mangroves on the coast of Tanjung Bunga Village, North Konawe. Mangrove restoration in the coastal area of Tanjung Bunga Village demonstrates that a collaborative and participatory approach can yield significant positive impacts in efforts to preserve a sustainable marine environment. It has been proven that by involving local communities in the mangrove restoration process, we not only protect the coastal ecosystem but also improve community welfare through the economic benefits that can be derived from the existence of that ecosystem.